LEADERSHIP FUNDAMENTALS FOR CYBERSECURITY IN PUBLIC POLICY AND ADMINISTRATION lessons for the global south. - Johnson, Donavon ([S.l.] : ROUTLEDGE, 2024)
In an increasingly interconnected and digital world, this book provides comprehensive guidance on cybersecurity leadership specifically tailored to the context of public policy and administration in the Global South. Author Donavon Johnson examines a number of important themes, including the key cybersecurity threats and risks faced by public policy and administration, the role of leadership in addressing cybersecurity challenges and fostering a culture of cybersecurity, effective cybersecurity governance structures and policies, building cybersecurity capabilities and a skilled workforce, developing incident response and recovery mechanisms in the face of cyber threats, and addressing privacy and data protection concerns in public policy and administration. Showcasing case studies and best practices from successful cybersecurity leadership initiatives in the Global South, readers will gain a more refined understanding of the symbiotic relationship between cybersecurity and public policy, democracy, and governance. This book will be of keen interest to students of public administration and public policy, as well as those professionally involved in the provision of public technology around the globe.
Keywords: Electronic government information -- Developing countries; Computer security; POLITICAL SCIENCE / Public Affairs & Administration